Proposed models for unit trust waqf and the parameters for their application. Issue 1 (17th June 2019) - Sulaiman, Syahnaz; Hasan, Aznan; Mohd Noor, Azman; Ismail, Muhd Issyam; Noordin, Nazrul Hazizi
Abstract : Purpose: This paper aims to present the viability of unit trust waqf (Islamic endowment) as an alternative asset class for waqf creation. Design/methodology/approach: This paper starts with the conceptual exploration of the literature in the areas of waqf. The sources of the literature cover authentic sources of the Qurʾān and ḥadīth, as well as secondary sources such as books, journal articles and online resources. Findings: This paper provides the conceptual framework of five models of unit trust waqf and their investment management parameters. Originality/value: The novelty of this paper lies in its attempt to highlight the importance of waqf investment strategy in ensuring sustainable returns for waqf. It does so by introducing the conceptual models of unit trust waqf as viable mechanisms to pool more cash waqf from individual investors. The sustainability of the capital waqf assets in the form of unit trusts is maintained through the parameters for its application proposed towards the end of the paper.